The relationship between political risk insurance policies and international investment agreements - Gupta, R (2018)
This thesis analyses the relationship between political risk insurance ("PRI") policies issued by public providers such as the Overseas Private Investment Corporation ("OPIC") and international investment agreements ("IIAs"). The analysis proceeds in three parts. Part I explains the basic features of the PRI industry and compares IIAs with PRI policies. Generally speaking, IIAs provide broad protections that are available to investors for free, whereas PRI policies provide specific and narrower protections, which are more effective and easier to enforce. Ultimately, both PRI policies and IIAs are risk-mitigation tools that should be evaluated together by investors at the time of making foreign investments. Part II explores the impact of PRI policies on the development of international law. Of particular importance are subrogation provisions found in most IIAs, which allow PRI providers to 'step into the shoes' of the investors and seek recovery from the host State. PRI providers should therefore take account of rights available to them under IIAs when assessing their recovery options. Further, as public insurers are government owned agencies, their actions give rise to State practice that may be relevant for interpretation of treaties in accordance with Articles 31(3)(a) and 31(3)(b) of the Vienna Convention on the Law of Treaties. Finally, Part III illustrates the contribution that OPIC jurisprudence can make to international law by studying specific determinations made by OPIC. Two OPIC determinations are particularly revealing: the Mid-American Holding/Indonesia Determination and the BoA/India Determination. In both cases, OPIC applied international law to determine whether the host State’s actions breached protections contained in the policies and, upon making payment to the investor, OPIC relied on international law to seek recovery fom the host States. Finallly, Part III analyses OPIC jurisprudence in the areas of attribution under international law and quantification of compensation – the analysis shows there is substantial scope for cross-fertilisation between OPIC’s jurisprudence and that of investment treaty tribunals.